2023
DOI: 10.59796/jcst.v13n2.2023.262
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial activity and silk dyeing of the crude pigment extract from J4 actinobacteria strain

Sittichai Urtgam,
Tawatchai Sumpradit,
Naruemol Thurnkul

Abstract: Actinobacteria represent a vast variety of prokaryotic microbes that produce a diverse group of secondary metabolites used in medical, agricultural, and industrial applications. The objectives in this study were to investigate the antibacterial activities and potential for silk dyeing of the crude extract from the actinobacterial strain J4. Initially, the antibacterial activities of the crude pigment extracts obtained from the actinobacterial strain J4 isolated from the wasp’s nest were determined. To extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Microorganisms produce many bioactive compounds such as carotenoids, melanins, flavins, and quinones. Filamentous fungi such as actinomycetes are a well-known producers of many pigments primarily used in the food and pharmaceutical industry [7][8][9]. In our present investigation, we have reported that actinomycetes are an economically and biotechnologically potential producers of natural dyes and pigments.…”
Section: Introductionmentioning
confidence: 62%
“…Microorganisms produce many bioactive compounds such as carotenoids, melanins, flavins, and quinones. Filamentous fungi such as actinomycetes are a well-known producers of many pigments primarily used in the food and pharmaceutical industry [7][8][9]. In our present investigation, we have reported that actinomycetes are an economically and biotechnologically potential producers of natural dyes and pigments.…”
Section: Introductionmentioning
confidence: 62%